Investigation the different ratios of carrier material to protect carotenoids in Gac (Momordica cochinchinensis Spreng) powder in drying process - Duyen, Nguyen Thi; Lam Diena, Le Khac; Minha, Nguyen Phuoc; Anh Daoa, Dong Thi (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
Momordica cochinchinensis Spreng, Cucurbitaceae, is indigenous to Southeast Asia and consumed there for dietary as well as medicinal uses. In Viet Nam, this plant is called Ga, and the seed membrane (seed pulp or aril) of the ripe fruit is widely used as a rice colorant due to its intense red color from its high carotene content. The aim of this study is to investigate the different ratios of carrier material to find out the appropriate ratio to protect carotene in Gac powder. The result shows that the most appropriate ratio of carier: Gac is 1: 1 (dry matter) in which the ratio of maltodextrin: gelatin is 0.5: 0.5 (w/w).